The Students English Achievement Perception and Attitude in English Language Teaching - Ajam, Ali; Rizal, Awaludin; Sahmadan, Safrudin; Ridayani, Ridayani (Journal of English Culture, Language, Literature and Education, 2023)
This correlation study aims to determine the following: 1 Students attitudes toward learning English are significantly correlated with achievement 2 Achievement and the quality of the English curriculum is strongly correlated with students perceptions of it 3 Achievement is significantly connected with opinions of the effectiveness of the English classroom and attitudes toward learning the language 276 data made up the population of this study One class out of the seven was chosen using a random cluster sampling method In one session thirty pupils were eligible for the analysis A perception survey an attitude survey and an achievement test were among the tools used to obtain the data Students perceptions of the caliber of English instruction and attitudes toward learning English were gathered using the perception and attitude questionnaires The perception and attitude questionnaire results were utilized to forecast English proficiency The data were analyzed with the use of numerous correlations and SPSS12 in order to accomplish the three goals of the current study The findings supported the notion that attitudes toward learning English and English achievement correlate with perceptions of English instruction s effectiveness The result of the computation of multiple correlation coefficients R is 767 and the correlation coefficient R2 is 588 Therefore perception and attitude accounted for 58 8 of the achievement leaving the remaining 41 2 unaffected by either According to the findings recommendations are made to EFL teaching professionals and other academics who wish to look into the subject more in the future These recommendations speak to the value of preserving perception and attitude in order to raise students English achievement < p>